Psychological Adjustment Of Saudi Arabian Postgraduate Students In Malaysia - Khalaf A., Alshammari Majid (2023)
The purpose of the present study is to investigate the psychological adjustment of Saudi Arabian Students in Malaysian universities and what are the contributed factors that affect it. In related studies, self-esteem, social support and language and cultural difficulties were the most suggested factors that affect the psychological adjustment of the international postgraduate students.